Enhanced Arctic Stratification in a Warming Scenario: Evidence From the Mid Pliocene Warm Period. Issue 6 (22nd June 2021) - Behera, Padmasini; Tiwari, Manish; Knies, Jochen
Abstract: Global warming is most pronounced in the Arctic as evident from the massive sea ice loss during the past few decades. The Mid‐Pliocene Warm Period (MPWP), 3.264 – 3.025 million years ago with similar CO2 levels, is the nearest analogue for understanding the impacts of future global warming. High‐resolution studies of relative nutrient utilization and productivity from the Atlantic‐Arctic Gateway (AAG) can provide insight into the nutrient availability governed by stratification strength during past warm climates. Here, we present relative nutrient utilization and productivity variability during the MPWP using sediments collected during the Ocean Drilling Program (ODP) Leg 151 from Fram Strait, AAG. We find that the relative nutrient utilization was high (low) implying stronger (weaker) stratification during warm (cold) periods during the MPWP. Stronger stratification inhibits the nutrient influx from intermediate water depths into the surface leading to higher utilization of available nutrients. It existed during warm periods likely due to enhanced summer sea ice melt and river discharge from the hinterland. As a consequence, the freshened surface layer could have stored more heat and accelerated the sea ice melt further implying that in the present‐day warm scenario, stronger stratification and upper layer freshening may lead to more sea ice melt in the Arctic Ocean. Key Points: First high‐resolution relative nutrient utilization record during Late Pliocene from Arctic Relative nutrient utilization is related to stratification at the study site Stronger (weaker) stratification found during warm (cold) periods of the Late Pliocene